A framework to support the design and cultivation of embedded research initiatives. (1st November 2021) - Ward, Vicky; Tooman, Tricia; Reid, Benet; Davies, Huw; O' Brien, Breid; Mear, Liz; Marshall, Martin
Abstract : Background: Embedded research involves co-locating researchers within non-academic organisations to better link research and practice. Embedded research initiatives are often complex and emergent with a range of underlying intents, structures and processes. This can create tensions within initiatives and contributes to ongoing uncertainty about the most suitable designs and the effectiveness of different approaches.Aims and objectives: We aimed to devise a practical framework to support those designing and cultivating embedded research by operationalising findings from an extensive study of existing initiatives.Key conclusions: The underpinning research on embedded initiatives ‐ a literature review and scoping exercise of initiatives in health settings across the UK ‐ showed that such initiatives share ten common sets of concerns in relation to their intent, structure and processes. We used these insights during a co-production workshop with embedded researchers and their managers that made use of a range of creative activities.The workshop resulted in a practical framework (and associated web-based tools) that draw on the metaphor of a garden to represent the growing, emergent nature of embedded research initiatives and the active work which individuals and organisations need to put into planning and maintaining such initiatives. Each of the aspects is represented as a separate area within the garden using relevant visual metaphors. Building on this, we also present a series of reflective questions designed to facilitate discussion and debate about design features, and we link these to the wider literature, thereby helping those involved to articulate and discuss their preferences and expectations.